An intercontinental analysis of food safety culture in view of food safety governance and national values. (May 2020) - Nyarugwe, Shingai P.; Linnemann, Anita R.; Ren, Yingxue; Bakker, Evert-Jan; Kussaga, Jamal B.; Watson, Derek; Fogliano, Vincenzo; Luning, Pieternel A.
Abstract: Taking food safety culture into account is a promising way to improve food safety performance in the food industry. Food safety culture (FS-culture) research is expanding from an organisational perspective to include characteristics of the internal and external company environment. In this study, the prevailing food safety culture in 17 food companies from four countries on three continents (Africa, Asia and Europe) was assessed in view of food safety governance and national values. The internal environment characteristics, i.e. food safety vision, food safety program and food production system vulnerability, were also assessed. Statistical analysis revealed little variation in FS-culture scores between the companies within the same country. Overall the FS-culture for Greek and Zambian companies was scored proactive, while for Chinese and Tanzanian companies an active score was achieved. Both the internal and external company environment seemed to influence the prevailing FS-culture. Cluster analysis showed that Tanzanian and Zambian companies exhibited similarities in the implementation of food safety programs, and in their national values and food safety governance as compared to Greece and China. Food safety governance was reflected in the food safety programs and supportiveness of the organisation to food safety and hygiene. All cultural dimensions were correlated with risk perceptions, with masculinity and long-term orientation also significantly correlated with the enabling conditions and attitude. Understanding how national values and food safety governance approaches differently influence food safety culture is expected to enable formulation of best approaches tailored for companies operating in countries with different company environments, to improve food safety performance. Highlights: Prevailing food safety culture is correlated with food safety performance. Knowledge of a company's environment is vital to understand its food safety culture. National values could have a role in an organisation's food safety culture.